LINKING ETHICAL LEADERSHIP TO GROUP PERFORMANCE - Dr. Avnish Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the present competitive world, organization achievement lies in group execution. It is accepted that group leads higher efficiency and better outcomes when contrasted with individual efforts however overseeing group dynamics and execution is another greatest challenge for leaders in present day's organizations. Research findings shows that a group with a positive dynamic is always desirable where group individuals trust each other, they progress in the direction of an aggregate choice, and they additionally consider each other responsible for getting things going. Then again, in a group with poor group dynamics, people's conduct interferes with work. Subsequently, the group may not go to any choice, or it might settle on the wrong decision, since group individuals couldn't investigate choices viably. An ethical leader can all the more likely set the standards and rules for keeping up positive and valuable group dynamic so as to accomplish organizational objectives. This conceptual paper is an endeavor to understand the job of ethical leaders in keeping up positive group dynamics, growing better intergroup relations and desirable group performance. This additionally discusses significant attributes, conduct and strategies of ethical leaders which may impact overall group performance.